Pengaruh Biaya Produksi dan Biaya Operasional Terhadap Laba Bersih Pada PT. Wilmar Cahaya Indonesia, Tbk. Tahun 2007-2023 - Merlin Ghardanova (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The purpose of this study was to determine the effect of production costs and operating costs on net income both partially and simultaneously at PT Wilmar Cahaya Indonesia, Tbk 2007-2023. The research method used is associative method, through secondary data collection with library studies of financial reports for 17 years from2007 to 2024, using multiple linear regression analysis, correlation analysis, t test and f test. The results of this study indicate that partially production costs have a significant effect on net income with a t test result value of 3,632, partially operational costs have no significant effect on net income with a t test result value of -1,024, andsimultaneously production costs and operational costs affect net income with a f test result value of 18,397.